2023
DOI: 10.3390/polym15020471
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of D-Limonene into O/W Nanoemulsions for Enhanced Stability

Abstract: The present study aimed to investigate the physical stability in terms of (droplet size, pH, and ionic strength) and chemical stability in terms of (retention) of D-limonene (LM) in the nanoemulsions after emulsification as well as after storing them for 30 days under different temperatures (5 °C, 25 °C, and 50 °C). LM is a cyclic monoterpene and a major component extracted from citrus fruits. The modification of disperse phase with soybean oil (SB) and a nonionic emulsifier (Tween 80) was adequate to prepare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…Different encapsulation techniques, such as spray drying, thin-layer drying, freezedrying, emulsification, coalescence, and ionic polymerization, have been used to improve the physicochemical properties and bioactivity of D-limonene to form polymeric materials, such as nanoemulsions, nanoparticles, nanogels, and microcapsules, whereas gum arabic, chitosan, alginate, and maltodextrins are common loading materials [25,186,[193][194][195][196][197][198].…”
Section: Nanotechnology: Improving Properties and Enhancing Bioactivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Different encapsulation techniques, such as spray drying, thin-layer drying, freezedrying, emulsification, coalescence, and ionic polymerization, have been used to improve the physicochemical properties and bioactivity of D-limonene to form polymeric materials, such as nanoemulsions, nanoparticles, nanogels, and microcapsules, whereas gum arabic, chitosan, alginate, and maltodextrins are common loading materials [25,186,[193][194][195][196][197][198].…”
Section: Nanotechnology: Improving Properties and Enhancing Bioactivitymentioning
confidence: 99%
“…In recent years, research on the practical applications of D-limonene has continued; however, despite its proven bioactivity, its hydrophobicity, volatility, and sensitivity to heat, light, oxygen, and moisture are affected by environmental factors (e.g., oxygen, light, and temperature) when applied directly to food systems and its oxidation gives off unpleasant odors, which, together with its own strong aromatic odor, can interfere with the sensory properties of the food to which they are added [22], which limits its application in food [23,24]. Currently, researchers are improving the physicochemical properties and bioactivity of D-limonene by producing new materials, such as nanoemulsions and nanofilms, through encapsulation and other techniques, and applying them in practical applications [25]. For instance, nanoemulsions of sodium caseinate and D-limonene in specific ratios were generated using high-pressure homogenization, which significantly improved preservation and thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that the nanoemulsion was stable under various conditions. The physical and chemical stability of nanoemulsions loaded with D-limonene was investigated by Sohan et al The physical stability of the nanoemulsion was observed over a period of 30 days, wherein the droplet size range remained consistent within the range of 122-130 nm [229].…”
Section: Microfluidizationmentioning
confidence: 99%